Oxidative Stress and Tissue Repair: Mechanism, Biomarkers, and Therapeutics - Gonçalves, Reggiani Vilela; Costa, Andrea M. A.; Grzeskowiak, Lukasz (Oxidative medicine and cellular longevity, 2021)
The excess of proinflammatory mediators promotes the increase of the peroxide of hydrogen (H2O2) and nitric oxide content, which accelerate the peroxidation of the component cells [7, 8]. [...]a controlled inflammation process is necessary to avoid persistent tissue damage through the continued action of free radicals and reactive oxygen species (ROS) [7]. [...]disruptors of redox balance (e.g., inductors of oxidative stress or inhibitors of antioxidant molecules) have been proposed as candidates for new healing drugs. The former study showed that nutrient intake and malnutrition can act as predictors of oxidative uremic toxicity. [...]they provided evidence that age and sex exhibited a limited association with malnutrition and cardiometabolic risk factors in haemodialysis patients. The latter study evaluated glutamine supplementation for the treatment of acute pancreatitis and showed that the use of glutamine might be promising for the future management of acute pancreatitis by relieving the intracellular energy stress, thereby attenuating the predominance of necrosis over apoptosis. [...]one review summarized the role of macroautophagy in the heart following myocardial infarction and showed that some noncoding RNAs and their easy manipulation exposed their potential as new targets for clinical development to treat autophagy-related diseases.